Analysis of Grab Online Motorcycle Taxi Application Usability in Jakarta Using PLS-SEM Approach Model - Elin Panca Saputra; Adila Faisal; Siti Nurajizah; Aryo Tunjung Kusumo; Tino Dwiantoro (Jurnal Infortech, 2026)
Founded in Singapore in 2012, Grab is one of the biggest online transportation companies in Southeast Asia. In Jakarta, GrabBike is part of this service. Even while technology advancements are driving the rise of these apps, issues including poor map accuracy, ugly UI, and frequently missed advertising still exist. Thus, the purpose of this study is to use the Technology Acceptance Model (TAM) to examine the variables that affect how simple it is to use the GrabBike service in Jakarta. Ease of use (Perceived Ease of Use), advantages (Perceived Usefulness), user attitude (Attitude Toward Using), user intention (Behavioral Intention to Use), and actual users (real System Usage) are the five study variables used in this method. Likert scale questionnaires were utilized to gather data from 106 individuals using a descriptive quantitative technique. The partial least squares (PLS)-based structural equation modeling (SEM) technique is used to assess the relationship between variables. The study's findings demonstrate that advantages (perceived usefulness) and usability (perceived ease of use) have a major impact on users' attitudes (attitude toward using). The intention to use (Behavioral Intention to Use) and Actual System Usage are subsequently impacted by this attitude.